Management of adults with diabetes on dialysis: Summary of recommendations of the Joint British Diabetes Societies guidelines 2022. Issue 4 (23rd December 2022) - Frankel, Andrew H.; Wahba, Mona; Ashworth, Vicky; Bedi, Rachna; Berrington, Rachel; Buckley, Maria; Chandrasekharan, Lakshmi; Doyle, Fiona; Duval, Deborah; Game, Frances; Hamilton, Susie; Hussain, Sufyan; et al.
Abstract: Diabetes is the commonest cause of end‐stage kidney disease in many parts of the world, and many people on dialysis programmes live with diabetes. Such people are vulnerable to complications from their diabetes, and their care may be fragmented due to the many specialists involved. This updated guidance from the Joint British Diabetes Societies aims to review and update the 2016 guidance, with particular emphasis on glycaemic monitoring in the light of recent advances in this area. In addition, the guidance covers clinical issues related to the management of diabetes in people on peritoneal dialysis, along with acute complications such as hypoglycaemia and ketoacidosis, and chronic complications such as foot and eye disease.